Electrochemical Zn2+-Li+ Substitution Method for Li+ Extraction from Brine with a High Mg2+/Li+ Ratio by the LiFePO4-Zn Cell System. Issue 3 (1st March 2023) - Han, Yuan; Wei, Yanan; Wu, Qiong; Li, Siqi; Xia, Junjie; Lu, Caiyou; Han, Yanling; Liu, Rongmei; Yang, Chao
Abstract : Electrochemical Li + extraction technology applied to salt lake brine has received considerable attention in recent years for its low energy consumption and low emissions. However, the current electrochemical Li + extraction method often requires the use of anion trapping electrodes or anion exchange membranes, which reduce their working lives and adaptabilities. To solve these problems, this study proposes a high Mg 2+ /Li + ratio brine electrochemical Li + extraction method based on the LiFePO4 -Zn battery system. By discharging in the brine and charging in a ZnCl2 solution, the Li + in the brine was successfully transferred to the ZnCl2 solution.